Severe Hypertriglyceridemia Induced Pancreatitis in Pregnancy. (3rd June 2014) - Gupta, Natasha; Ahmed, Seema; Shaffer, Lemuel; Cavens, Paula; Blankstein, Josef
Abstract : Acute pancreatitis caused by severe gestational hypertriglyceridemia is a rare complication of pregnancy. Acute pancreatitis has been well associated with gallstone disease, alcoholism, or drug abuse but rarely seen in association with severe hypertriglyceridemia. Hypertriglyceridemia may occur in pregnancy due to normal physiological changes leading to abnormalities in lipid metabolism. We report a case of severe gestational hypertriglyceridemia that caused acute pancreatitis at full term and was successfully treated with postpartum therapeutic plasma exchange. Patient also developed several other complications related to her substantial hypertriglyceridemia including preeclampsia, chylous ascites, retinal detachment, pleural effusion, and chronic pericarditis. This patient had no previous family or personal history of lipid abnormality and had four successful prior pregnancies without developing gestational hypertriglyceridemia. Such a severe hypertriglyceridemia is usually seen in patients with familial chylomicronemia syndromes where hypertriglyceridemia is exacerbated by the pregnancy, leading to fatal complications such as acute pancreatitis.